Development of an effective educational computer game based on a mission synchronization-based peer-assistance approach. Issue 5 (4th July 2017) - Chang, Shao-Chen; Hwang, Gwo-Jen
ABSTRACT: In this study, a mission synchronization-based peer-assistance approach is proposed to improve students' learning performance in digital game-based learning activities. To evaluate the effectiveness of the proposed approach, an experiment has been conducted in an elementary school natural science course to examine the participants' learning attitudes, collaboration skills, and learning achievements. From the experimental results, it was found that the educational game with the mission synchronization-based peer-assistance mechanism not only benefited the students in terms of promoting their learning achievements and attitudes, but also improved their collaboration skills via encouraging them to actively provide assistance to their peers during the gaming process. Finally, to further investigate the factors that might affect the performance of the mission synchronization-based peer-assistance approach, the students' learning behaviors are summarized and discussed.